Complementarity of indigenous and western scientific approaches for monitoring forest state. Issue 7 (28th August 2018) - Lyver, Phil O'B.; Richardson, Sarah J.; Gormley, Andrew M.; Timoti, Puke; Jones, Christopher J.; Tahi, Brenda L.
Abstract: Cross‐cultural environmental monitoring systems inform on a broad suite of indicators relevant to both scientific and local communities. In this study, we used forest‐plot‐based survey measures developed by western scientists and a set of community‐based survey indicators developed by Māori, the indigenous people of New Zealand (NZ), to compare the current state of two ecologically congruent forests (Whirinaki and Ruatāhuna), as they related to a historic Ruatāhuna forest state (Baseline; 1955–1975) in NZ. Both the plot‐based and community‐based field surveys indicated that the Whirinaki forest was in a better state than the Ruatāhuna forest. This was supported by a stronger mauri (concept of life essence) rating assigned by Māori elders to the Whirinaki forest compared with the Ruatāhuna forests. However, both the Ruatāhuna and Whirinaki forests were deemed to be in a significantly poorer state than the Baseline forest. A cross‐cultural monitoring system provides understanding of forest state that both managers and communities can use for decision‐making. Historical baselines of forest state can provide ecological targets for restoration initiatives and also identify where on the restoration continuum current forest indicators lie. The alignment of plot‐based measures with community‐based indicators offers possibilities for future‐proofing a cross‐cultural monitoring system and buffering it from intergenerational shifts in ecological baselines. The opportunity for indigenous peoples and local communities to apply their traditional ways of knowing, and interpret and act on information they understand are crucial components of cross‐cultural environmental management regimes.